Social Competence in the 65+ Population - Vítečková, Miluše; Procházka, Miroslav; Kamanová, Lenka (Mendel University in Brno, 2025)
This paper examines social competence in the 65+ population based on a qualitative study involving 25 participants aged 65 and older. The research defines social competence as the ability to initiate and maintain meaningful social interactions. The study is part of a broader project Support and development of financial, digital, social, and health literacy among the 65+ population (TAČR, TQ01000591). Through in-depth interviews, the study identified areas of social competence deficits. Participants described challenging situations in their social interactions, recognizing their own limitations and describing how they try to address them when dealing with people or institutions. Many expressed feelings of feelings of resignation or submission in demanding social contexts. The most common social barriers included shyness, low assertiveness, fear of rejection or criticism, and, in some cases, overly aggressive responses. These behaviors often stem from a lack of support or targeted educational opportunities. The findings suggest that older adults face specific social challenges that may impede their daily activities and overall well-being. The identified barriers offer valuable insights for developing educational programs aimed at strengthening social competence among older adults.
Keywords: social competence; 65+ generation; social interactions; qualitative survey